Changes in wine-growing areas by wine-growing districts and subdistricts in Slovenia in the period 2000-2019 - Žiberna, Igor (Journal for Geography, 2019)
The article analyses changes in wine-growing areas in the area of wine-growing districts and subdistricts in Slovenia in the period 2000-2019. Viticulture has represented an important sector in Slovenian farms since the ancient age. In recent decades, wine-growing is associated with a tourism. Wine-growing areas are shrinking everywhere, and the problem is the growing age of vineyards, as their renovation is linked to high costs. There are significant differences between wine-growing districts and subdistricts in Slovenia in the stages of the abandonment of winegrowing areas.